Potential of Implementing Artificial Intelligence (AI) for Reducing Waste at Construction Site - Tan , Wan Yuan; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2024)
This research presents the potential implementation of Artificial Intelligence (AI) to reduce construction waste in Johor, Malaysia. Most of the construction and demolition wastes in Johor, Malaysia are not recycled but are eventually dumped and landfilled, which may have serious environmental consequences and require the construction of more landfills in the future. Therefore this research focuses on the potential of implementing Artificial Intelligence (AI) to reduce construction waste in the construction industry in Johor, Malaysia. The main objectives of this research are to investigate the current practice of construction waste management in the construction industry, the challenges of implementing Artificial Intelligence (AI) in the construction industry, and the potential of implementing Artificial Intelligence (AI) to reduce construction waste in the construction industry. The respondents of this study are G5, G6, and G7 contractors from the state of Johor. The population of G5, G6, and G7 that registered with the CIDB are total 1618 and the number of responses is 154 which contributed to 9.54%. The quantitative method is used to reach the objective of this research. The data and information was analyzed by using Statistical Package for Social Sciences (SPSS). At the end of the research, there are most of the respondents are agree that implementing AI in the construction industry able to reduce waste generation during the construction process. Besides, most of the respondents also said that there are still many obstacles to the adoption of Artificial Intelligence (AI) in the Malaysian construction industry and that Artificial Intelligence (AI) really can change the current practice in construction waste management. Lastly, this study is very useful for the construction industry development in the future. This research can provide sustainability for the environment.